2007
DOI: 10.1016/j.brainres.2006.10.086
|View full text |Cite
|
Sign up to set email alerts
|

The ataxic groggy rat has a missense mutation in the P/Q-type voltage-gated Ca2+ channel α1A subunit gene and exhibits absence seizures

Abstract: The groggy rat (strain name; GRY) exhibits ataxia, an unstable gait, and paroxysmal severe extension of the entire body. Adults show a reduction in size of the cerebellum and presynaptic and axon terminal abnormalities of Purkinje cells. These neurological abnormalities are inherited in an autosomal recessive manner, and the causative mutation has been named groggy (gry). In this study, we mapped gry on rat chromosome 19 and found a nonconservative missense (M251K) mutation in the alpha(1A) subunit of the P/Q-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 37 publications
1
42
0
Order By: Relevance
“…34 Among the subtypes of human SCDs, SCA6 is caused by an elongated CAG repeat of the CACNA1A gene encoding the P/Q-type voltagedependent calcium channel. 13 Several murine models with mutations at the a1 subunit of the gene such as groggy rat 49,52 are thought to have some clinical and pathologic similarity with canine NAD. To discuss the relationship between the calcium channel and canine NAD, further molecular investigations, including gene analysis, are necessary.…”
Section: Discussionmentioning
confidence: 99%
“…34 Among the subtypes of human SCDs, SCA6 is caused by an elongated CAG repeat of the CACNA1A gene encoding the P/Q-type voltagedependent calcium channel. 13 Several murine models with mutations at the a1 subunit of the gene such as groggy rat 49,52 are thought to have some clinical and pathologic similarity with canine NAD. To discuss the relationship between the calcium channel and canine NAD, further molecular investigations, including gene analysis, are necessary.…”
Section: Discussionmentioning
confidence: 99%
“…A spontaneous recessive mutation in CACNA1A was identified in the groggy (GRY), which shows absence seizures similar to the tottering mouse series, ataxia, and paroxysmal dyskinesia. The mutation, M251K, located close to the ion selective pore is associated with a small cerebellum and abnormalities of Purkinje cells (Tokuda et al 2007). …”
Section: Calcium Channels and Epilepsymentioning
confidence: 99%
“…Surgical procedures for the electrode implantation and EEG recordings were performed as described previously (20,22). Since it was confirmed in the preliminary experiments that both male and female rats exhibited SWD with a similar frequency, GRY rats of either sex (250 -350 g) were employed.…”
Section: Drug Treatments and Eeg Recordingmentioning
confidence: 99%
“…More recently, Tokuda et al (20) showed that GRY rats carry a missense (M251K) mutation in the gene encoding the α 1A subunit of the P/Q type voltage-dependent Ca 2+ channel (Cacna1a) and, like the Cacna1a mutant tottering mice (21), exhibit absence-like seizures associated with 7 -8 Hz spike and wave discharges (SWD) and concomitant immobile postures. In addition, absence-like seizures in GRY rats were significantly alleviated by two antiepileptic drugs effective for human absence seizures, ethosuximide and sodium valproic acid, but not by phenytoin that lacks efficacy for absence seizures (20). These analyses of seizure phenotypes reveal that GRY rats are useful as a novel model of human absence epilepsy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation